2021
DOI: 10.3390/antiox10101614
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Inhibitory Effect on Nitric Oxide Production of Hydroponic Ginseng Fermented with Lactococcus lactis KC24

Abstract: Panax ginseng Meyer is used as a medicinal plant. The aim of this study was to ferment hydroponic ginseng with Lactococcus lactis KC24 and confirm its antioxidant activity and inhibitory effect on nitric oxide (NO) production. Flavonoid and phenol contents in fermented ginseng extracts were measured. Antioxidant activity was measured by DPPH, ABTS, reducing power, FRAP and β-carotene assays. Additionally, inhibitory effects on NO production and toxicity of the fermented extract were determined using RAW 264.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…in L. rhamnosus -fermented extract [ 15 ]. Chung et al showed that the total phenolic contents in 12-h and 24-h fermented ginseng extracts with Lactococcus lactis KC24 increased by 6.1% and 4.1%, respectively, and were greater than in nonfermented extracts [ 54 ]. Moreover, Antognoni et al used different lactic acid bacteria strains to ferment wheat ( Triticum aestivum L. ) and detected ferulic, p-coumaric, cinnamic, caffeic, sinapic, p-hydroxybenzoic, and gallic acids in the fermented dough [ 50 ].…”
Section: Changes Of Antioxidant Constituents In Plant-based Food Materials During Fermentationmentioning
confidence: 99%
“…in L. rhamnosus -fermented extract [ 15 ]. Chung et al showed that the total phenolic contents in 12-h and 24-h fermented ginseng extracts with Lactococcus lactis KC24 increased by 6.1% and 4.1%, respectively, and were greater than in nonfermented extracts [ 54 ]. Moreover, Antognoni et al used different lactic acid bacteria strains to ferment wheat ( Triticum aestivum L. ) and detected ferulic, p-coumaric, cinnamic, caffeic, sinapic, p-hydroxybenzoic, and gallic acids in the fermented dough [ 50 ].…”
Section: Changes Of Antioxidant Constituents In Plant-based Food Materials During Fermentationmentioning
confidence: 99%
“…Therefore, LABs can increase the concentration of phenolic compounds and enhance their bioaccessibility and bioavailablity 25 . According to Chung et al 20 . H12F and H24F contain increased phenolic compounds and flavonoids, which exhibit strong antioxidative effects, compared with HNF 20,26 .…”
Section: Resultsmentioning
confidence: 99%
“…25 According to Chung et al 20 H12F and H24F contain increased phenolic compounds and flavonoids, which exhibit strong antioxidative effects, compared with HNF. 20,26 This is because rutin, an abundant polyphenol in ginseng, could be converted into a kaempferol-3-rutinoside intermediate via enzymatic degradation during fermentation. 27 Moreover, transformation of major ginsenosides, which constitute 80% of the total ginsenosides, can produce minor ginsenosides, which aid in pharmaceutical activities by structural changes.…”
Section: Resultsmentioning
confidence: 99%
“…paracasei cek-R2 , and Lentilactobacillus otakiensis cek-R3 [ 87 ]. In addition, fermented root vegetables, due to lactic acid-producing bacteria, showed increased inhibition of pathogenic strains such as Listeria monocytogenes and Staphylococcus aureus [ 88 ].…”
Section: Microbiological Composition Of Fermented Vegetablesmentioning
confidence: 99%